Some issues of the ensuring of rights and legal interests of persons at the interrogation by the videoconference at the pre-trial investigation - Шингарьов, Денис Олександрович (Problems of legality, 2016)
The article is connected with the analysis of rules of the current CPC of Ukraine which regulated the application of videoconference at the interrogation at the pre-trial investigation. The research has showed that there are some problem aspects of ensuring of the rights and legal interests of the participation of criminal proceedings. First of all, such right of suspect as a refusing of giving testimonies can’t be realized fully, because there is not any procedure, which provides getting of such refuse by the investigator or a prosecutor, who situates remotely from suspect. At the same time, the official, who is situated near the suspect can’t get this refuse, because he hasn’t such competency. Also there are some problems with the engaging of the specialist to the interrogation with the application of videoconference. There is not compulsory demand to the officials who are providing this investigative action to engage such participation of criminal proceedings. But the absence of the specialist can lead to the impossibility providing of interrogation in the conditions of quality sound, image and the information security.